Some Scientific Customary Health Practices of Hindu Brahmins of Nalbari and Barpeta Districts of Assam, India - Hiranmaya Sharma (Dera Natung Government College Research Journal)
The customary practices among various communities are a result of accumulation of knowledge of many generations over a long period of time. Many customary practices are associated with the health of human in some way. The Assamese Brahmins also practice many customary health practices, which affect the overall health of the human body in many ways. In this study, the customary health practices of Brahmins of Nalbari and Barpeta districts of Assam have been studied. Many practices related to various daily and seasonal activities are prevalent among the Assamese Brahmins. Some such practices are associated with daily activi- ties like cooking, bathing and eating. Customary practices associated with seasonal activities like festivals, Puja and Naam-Kirtan also finds an important place in their lifestyle. Modern day research has elaborated the scientific bases of many such practices followed by Assamese Brahmins. Some practices like fasting can help in keeping the body metabolism in check, leading to a healthy life. Many practices related to children, women and men helps in maintaining the childhood ailments, pregnancy and overall health of the people. The stringent customary practices, which are hard to follow in the present day world, are losing the frequency of use during the present days, leading to extinction of such practices, which evolved over long periods of time. Such customary practices can be utilized effectively for preventing present day ailments and also for cure without the use of any additional medicines or medical therapy.